Becker′s nevus syndrome - Sathyanarayana B Dasegowda (Indian Journal of Dermatology, 2014)
Becker′s nevus is a cutaneous hamartoma characterized by circumscribed hyperpigmentation with hypertrichosis. Becker′s nevus syndrome is an association of Becker′s nevus with unilateral breast hypoplasia and muscle, skin, and/or skeletal abnormalities. We here report a case of a 15 year-old female who presented with bilateral Becker′s nevus over her groins, thighs, vulva, and in front of the neck from the age of 5 years. She had associated mental retardation, delayed development of mile stones, delayed puberty, dwarfism, depressed nasal bridge, long slender digits, crowding of lateral toes, valgus deformity of first metatarsophalangeal joint, mitral valve prolapse, muddy conjunctiva with hypertrophic and hyperpigmented caruncle of both eyes, ichthyosis, brownish hair, and absence of axillary and pubic hair. On histopathological examination collagen hamartoma underneath the Becker′s nevus was found.